Recurrence of febrile seizure in Yazd, Iran - Fallah, Razieh; Karbasi, Sedighah Akhavan (The Turkish Journal of Pediatrics, 2010)
Febrile seizure (FS) is the most common problem in pediatric neurology. The purpose of this study was to determine FS recurrence frequency and to evaluate its risk factors. In a descriptive retrospective study, 139 children with first FS, admitted between March 2004 and August 2005 in Yazd Shaheed Sadoughi Hospital, were followed. Seventy-six boys and 63 girls with a mean age of 2.03 +/- 1.21 years were followed for 25.1 +/- 5.5 months. Thirty-seven percent had FS recurrence, with a mean recurrence time of 6.7 +/- 5.9 months. Sixty-five percent of infants and 30% of children >1 year old had FS recurrence. Sixty-three percent of those with seizure occurring in 1 hour of fever duration had FS recurrence. Seizures in children